Design of Augmented Reality-Based Learning Media for English Vocabulary Learning at Elementary School - Dian Syafitri Chani Saputri, Zulfiati Syahrial, Khaerudin (International Journal of Advanced Science and Technology, 2020)
Augmented Reality is able to create new ways of utilizing technology to facilitate learning and improve performance. This technology has been used as a learning medium for learning vocabulary in English at the elementary school level. However, the Augmented Reality learning media has not been prepared following the syllabi applied by the school. This study presented the design of AR-based learning media to learn vocabulary that is interesting, rich in content, meets syllabi needs and can facilitate learning. Learning media are developed using the Multimedia based Instructional Design development model according to Lee and Owens. Developed learning media has rich multimedia content and consider the principles in design instructional. The results of this study released assessment and front-end analysis reports and application design. Assessment and front-end analysis described user analysis, technology analysis, task analysis, and issue analysis. While, application design reported media specification, course flowchart, and lesson flowchart. This study concluded an augmented reality-based learning media potential to be one of the learning media to teach English vocabulary in elementary school.